Which treatment of the subcondylar fractures results on a more effective bite force recovery?. (October 2021) - Costa, S.; Campos Ribeiro, B.; Figueiredo Amaral, M.
Abstract : Purpose: Mandibular condyle fractures presents different classifications and treatment modalities. It is controversial if the open surgery presents a more effective recover of the mandibular function than the closed treatment. Methods: A prospective cohort was performed aiming to measure the bite force and maximum mouth opening in two groups, surgical and closed treatment, in seven to ninety days after the procedure. The bite force was measured using a specific designed dynamometer. Results: A total of twelve patients were included in this study, six in each group. The maximum mouth opening was recovered after the day 30 on patients on the surgical group, on the closed treatment group it occurred on the sixtieth day, a statistical significant difference, p=0, 003. The bite force was regained in both groups with a mean time of thirty days and there was no difference between the groups, p=0, 766. Conclusion: Both techniques are reliable in the long term and no differences were observed in the 2-plates AO/ASIF technique and the closed treatment for the subcondylar fractures on the bite force. However, the surgery recovers the patient's mouth opening in a less time.